HUBUNGAN KADAR KALIUM, KALSIUM, DAN FOSFOR ANORGANIK PADA PENDERITA GAGAL GINJAL - Tri Prasetyorini Prasetyorini; Warida Warida Warida (Poltekkes Kemenkes Jakarta III, 2015)
The prevalence of patients renal failure is quite high due to factors of unhealthy lifestyle, food, herbal medicines, microorganisms and other toxic materials nefro. To determine the damage of kidney function can be carried out uric acid and creatinine laboratory tests, whereas for monitoring can be done by checking electrolytes including potassium, calcium and phosphorus levels inorganic. Normality value of calcium and inorganic phosphorus has a reciprocal relationship and called pathognomonic. The purpose of this study was to determine its relationship with the percentage of potassium, calcium and inorganic phosphorus in patients. The research using secondary data, with a total sample of 102 medical records from the patients with renal failure in East Jakarta Islamic Hospital from January to December 2012. The results of this study in men as much as 71.57 % and by as much as 28.43 % of women who experienced a 14 % hypokalemia , hyperkalemia 5 % with an average value of 4.15 mEq / L, 10 % experienced hypocalcemia , hypercalcemia 38 % and the average value of 4.61 mg / dL , while 41 % were experiencing hypophosphatemia , hyperphosphatemia 10 % and the average value of 9.01 mg / dL. After Kendall correlation test value 0.017 is obtained which shows there is a correlation between the levels of Calcium to Inorganic Phosphorus Levels.